Quantitative resistance against Bemisia tabaci in Solanum pennellii: Genetics and metabolomics. Issue 4 (19th January 2016) - van den Oever‐van den Elsen, Floor; Lucatti, Alejandro F.; van Heusden, Sjaak; Broekgaarden, Colette; Mumm, Roland; Dicke, Marcel; Vosman, Ben
Abstract: The whitefly Bemisia tabaci is a serious threat in tomato cultivation worldwide as all varieties grown today are highly susceptible to this devastating herbivorous insect. Many accessions of the tomato wild relative Solanum pennellii show a high resistance towards B. tabaci . A mapping approach was used to elucidate the genetic background of whitefly‐resistance related traits and associated biochemical traits in this species. Minor quantitative trait loci (QTLs) for whitefly adult survival (AS) and oviposition rate (OR) were identified and some were confirmed in an F2 BC1 population, where they showed increased percentages of explained variance (more than 30%). Bulked segregant analyses on pools of whitefly‐resistant and ‐susceptible F2 plants enabled the identification of metabolites that correlate either with resistance or susceptibility. Genetic mapping of these metabolites showed that a large number of them co‐localize with whitefly‐resistance QTLs. Some of these whitefly‐resistance QTLs are hotspots for metabolite QTLs. Although a large number of metabolite QTLs correlated to whitefly resistance or susceptibility, most of them are yet unknown compounds and further studies are needed to identify the metabolic pathways and genes involved. The results indicate a direct genetic correlation between biochemical‐based resistance characteristics and reduced whitefly incidence in S. pennellii . Abstract : Whitefly Bemisia tabaci is a serious threat in worldwide tomato cultivation. Some wild relatives of tomato show resistance to the whitefly. We identified a strong source of resistance in Solanum pennellii . The genetic and biochemical basis of the resistance were analysed and metabolites linked to the resistance were identified.